Effect of Lactiplantibacillus plantarum X22-2 on Biogenic Amine Formation and Quality of Fermented Lamb Sausage during Storage - Ting Liu; Taiwu Zhang; Yujia Zhai; Lina Sun; Maoqin Zhai; Letian Kang; Xin Zhao; Bohui Wang; Yan Duan; Ye Jin (Fermentation, 2023)
In this study, the safety of fermented lamb sausage was examined. The aim was to investigate the effect of Lactiplantibacillus plantarum X22-2 (LP X22-2) on the quality of, and biogenic amine (BA) formation in, fermented lamb sausages during fermentation, maturation, and storage. The results showed that LP X-22 was effective in increasing the number of lactic acid bacteria (LAB) and in significantly inhibiting the formation of putrescine, histamine, cadaverine, and tyramine in fermented lamb sausage (p < 0.05). The total volatile basic nitrogen (TVB-N) content, peroxide value (POV) of fat, pH, water activity (AW), and viscosity were lower in the LF group compared to other groups (commercial starter group—CF, and natural fermentation group—NF) (p < 0.05). Furthermore, sensory evaluation and texture profile analysis (TPA) indicated that LP X-22 significantly increased the a* value, chewiness, and hardness of the sausages (p < 0.05). Therefore, LP X-22 is recommended as a natural and safe protective culture for preserving fermented lamb sausage and maintaining the color of the sausages while improving their sensory quality and inhibiting the accumulation of BAs.